Executive Entrepreneurship in National Departments. Issue 6 (July 2019) - Berman, Evan M.; Chen, Don-Yun; Wang, XiaoHu; Liu, Ivy
Leadership by senior public managers in national departments is increasingly called for in response to many policy challenges and limitations of appointee and political leadership. This study defines "executive entrepreneurship" as senior, career public managers furthering new policies and initiatives, with input from stakeholders and support from political appointees. Study results from a dyadic survey of executives reporting directly to (deputy) ministers show that executive entrepreneurship is significantly furthered by (a) executives' commitment to public causes, (b) orientation of appointees to their obligations and agency roles, and (c) external accountability of department performance. Implications are discussed for future studies.